Comparative analysis of peptidoglycan recognition proteins in endoparasitoid wasp Microplitis mediator. (11th February 2016) - Wang, Rui‐Juan; Lin, Zhe; Jiang, Hong; Li, Jiancheng; Saha, Tusar T.; Lu, Ziyun; Lu, Zhiqiang; Zou, Zhen
Abstract: Peptidoglycan recognition proteins (PGRPs) are a family of innate immune receptors that specifically recognize peptidoglycans (PGNs) on the surface of a number of pathogens. Here, we have identified and characterized six PGRPs from endoparasitoid wasp, Microplitis mediator (MmePGRPs). To understand the roles of PGRPs in parasitoid wasps, we analyzed their evolutionary relationship and orthology, expression profiles during different developmental stages, and transcriptional expression following infection with Gram‐positive and ‐negative bacteria and a fungus. MmePGRP‐S1 was significantly induced in response to pathogenic infection. This prompted us to evaluate the effects of RNA interference mediated gene specific knockdown of MmePGRP‐S1 . The knockdown of MmePGRP‐S1 (iMmePGRP‐S1) dramatically affected wasps' survival following challenge by Micrococcus luteus, indicating the involvement of this particular PGRP in immune responses against Gram‐positive bacteria. This action is likely to be mediated by the Toll pathway, but the mechanism remains to be determined. MmePGRP‐S1 does not play a significant role in anti‐fungal immunity as indicated by the survival rate of iMmePGRP‐S1 wasps. This study provides a comprehensive characterization of PGRPs in the economically important hymenopteran species M. mediator .